Seleksi Terbuka Perangkat Desa (Studi Kasus: Desa Sendang Sari Kabupaten Kulon Progo dan Desa Panggung Harjo Kabupaten Bantul Tahun 2017) - Hafieludin, Muhammad; Atmojo, Muhammad Eko (Jurnal Ilmu Administrasi Negara (JUAN), 2020)
Open selection for village devices is an innovation in improving the quality of village apparatus resources. With the improvement of the quality of the village apparatus is expected to improve the public services for the community. Considering the demands of the village government at this time is increasing, especially in terms of public services and in the order of government-based good governance. This research will be conducted in two villages to perform a comparison in the implementation of open selection. Where in the implementation of research using qualitative research methods, the techniques used are in-depth interviews and documentation. The results showed that the implementation of open selection for the village apparatus was very useful and went well. However, in the implementation of open selection there is a difference between the village Sendangsari and Panggungharjo village. The implementation of open selection in Sendangsari village only uses written exams, while for open selection in Panggunharjo village using written exams, practice exams, psychological tests, and interviews. It shows that in improving the quality and competence of the village employees are very popular, but the hope remains the same that is to get the resources of the village apparatus that has competence, professional and integrity.